The Effect of Product Quality, Personal Sales and Prices on CPO Purchasing Decisions at PT Kencana Persada Nusantara Medan: The Effect of Product Quality, Personal Sales and Prices on CPO Purchasing Decisions at PT Kencana Persada Nusantara Medan - Ferdian Ferdian; Stefie Stefie; Januardi Januardi (Institute of Computer Science (IOCS), 2020)
This research conducted in PT Kencana Persada Nusantaa Terrain that has a long standing and reputable engaged in oil palm. In this study aims to be able to analyze the quality of the product, personal selling and the price of the CPO purchase decision on PT Kencana Persada Nusantara Medan. The decrease in sales of CPO purchase decisions due to the quality of products, personal selling and the price of CPO. Population and sample in this research berjumlaj 76 CPO customers.The research method using multiple linear regression analysis. The results of partial hypothesis testing researchobtainablesimultaneously Quality Products, Personal Selling and Pricing positive and significant impact on CPO Purchase Decision on PT. Kencana Persada Nusantara Medan and partially Quality Products, Personal Selling and Pricing positive and significant impact on CPO Purchase Decision on PT. Kencana Persada Nusantara Medan. Hacyl coefficient determination Rsquare Adjusted values ??obtained for 0.322 this means that 32.2% of the variation of the dependent variable is the purchase decision can be explained by variations in the independent variable is free kualita products, personal selling and hargasedangkan the remaining 67.8% is explained by other variables not examined in this study, such as product differentiation, product innovation, product attributes and so on,